Hubungan Aktivitas Fisik Terhadap Kejadian Premenstrual Syndrome Pada Remaja Puteri Siswi Kelas XI SMA Assanadiyah Palembang Tahun 2021 - M. Iman Tarmizi Thaher; Erike Septa Prautami; Putri Ulama (Universitas Pahlawan Tuanku Tambusai, 2022)
Premenstrual syndrome is a condition where a number of symptoms occur regularly and are related to the menstrual cycle, symptoms usually appear 7-10 days before menstruation begins. The aim of this study was to find out the relationship between physical activity and the incidence of premenstrual syndrome in young women at SMA Assanadiyah Palembang in 2021. The research used the analytical survey method with a cross sectional study approach. The research population was all young women totaling 63 respondents. The results of the univariate analysis of young women who did less light activities, namely 31 (49.2%), young women who did not do more light activities, namely 32 (50.8%). There were fewer girls who did moderate activities, namely 17 (27.0%), while there were more girls who did not do moderate activities, namely 46 (73.0%). Young women who did less strenuous activities, namely 15 (23.8%), while young women who did not do more strenuous activities, namely 48 (76.2%). Young women who experienced premenstrual syndrome were more, namely 51 (81.0%), young women who did not experience premenstrual syndrome were fewer, namely 12 (19.0%). Statistical test results with Chi-Square obtained р_value 0.021 meaning α <(0.05) so there is a significant relationship between light activity and the incidence of premenstrual syndrome in young women. The Chi-Square statistical test obtained a р_value of 0.155 meaning α > (0.05) so that there is no significant relationship between moderate activity and the incidence of premenstrual syndrome in young women. The Chi-Square statistical test obtained a р_value of 0.264 meaning α > (0.05) so there is no significant relationship between strenuous activity and the incidence of premenstrual syndrome in young women. It is hoped that other researchers researching the same topic should add other variables and add more samples and populations. Keywords: Premenstrual Syndrome, Physical Activity